URBAN PLANNING, ARCHITECTURE AND GLOBAL TERRORISM: THE NIGERIAN PERSPERCTIVE - Usip, Elijah; Edem, Timothy Effiong; Etuk, Uyobong (European Scientific Journal, ESJ, 2015)
Man’s fear of insecurity, violence, death and destruction has been intensified beyond measures in 21st century due to the frequency, intensity and spread of global terrorism. Homes, public infrastructures and facilities have been destroyed, physical and psychological injuries inflicted, economic fortunes wrecked in a moment, many displaced and lives lost as a result of terrorism and threats to terrorism. Different countries and regions respond differently to terrorism/threats to terrorism due to diversity in technological advancement, communication/information dissemination and technology, socio-cultural development, economic strength and multilateral relationships. However one area counterterrorism strategy has been identical globally is in urban planning and architecture. Different civilizations have witnessed peculiar urban planning policies and designs that influenced their space arrangement to achieve basic elements of urban planning. Given the prevalence of terrorism, public facilities and potential targets are now designed, structured and operated to offer maximum safety and security to the users, and also restrict entrance in order to control access, promote security checks, and surveillance, and ensure timely intervention in case of any attacks/threats. Metadata methodology of research was adopted for the study. In this approach, research findings and existing literatures were used for the analysis, and it reveals that urban planning policies, architecture of fear and resilient cities development are practicable in Nigeria. However there arises a gap for more research on the cultural implications these counterterrorism strategies. This paper examined the reaction of urban planning and architecture to the presence of global terrorism in Nigeria.